2016
DOI: 10.1177/1478210316642675
|View full text |Cite
|
Sign up to set email alerts
|

Learning how to do up buttons: Professionalism, teacher identity and bureaucratic subjectivities in early years settings

Abstract: Early years education in Europe and elsewhere around the world is currently in the spotlight due to political and economical changes and subsequent promises of effective investment into its provision. In this article we analyse everyday preschool practices in Slovakia in terms of tensions between policies, the teachers workforce and the concept of professionalism. Through bureaucratic scientisation, teachers become subjects with bureaucratic subjectivities, and they are expected to devote increasing amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This tension and conflict may relate to the early years practitioners' own professional identities (Osgood 2006(Osgood , 2012Manning-Morton 2006;McDowall Clark and Baylis 2012). In fact, Pupala, Kascak and Tesar (2016) propose that this is a 'contemporary' (p. 656) viewpoint, suggesting that there are now many 'new educational challenges and criteria that early years education is increasingly expected to fulfil' (p. 656). However, early reading has not usually been described as a 'new educational challenge', given that reading stories and sharing books from birth onwards has already been well documented by researchers (Clark 2014; Elkin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This tension and conflict may relate to the early years practitioners' own professional identities (Osgood 2006(Osgood , 2012Manning-Morton 2006;McDowall Clark and Baylis 2012). In fact, Pupala, Kascak and Tesar (2016) propose that this is a 'contemporary' (p. 656) viewpoint, suggesting that there are now many 'new educational challenges and criteria that early years education is increasingly expected to fulfil' (p. 656). However, early reading has not usually been described as a 'new educational challenge', given that reading stories and sharing books from birth onwards has already been well documented by researchers (Clark 2014; Elkin 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As a further protection of contributor identities, all names and settings have been altered, so the quotes do not identify particular individuals, settings or localities. These complexities have also been explored elsewhere (Pupala, Kascak, and Tesar 2016).…”
Section: Methodsmentioning
confidence: 99%
“…It is a burden that threatens their identity and is felt to be a departure from their original role, which they see as participation in children's learning. (It is not necessarily like this, though, as some of our research has shown that teachers incorporate bureaucratic tasks into their professional identity and consider the successful handling of bureaucracy to be a mark of their identity) [6].…”
Section: Literature Review and Discussionmentioning
confidence: 99%